Sublethal concentrations of antibiotics enhance transmission of antibiotic resistance genes in environmental Escherichia coli - Gray-Hammerton, Charlotte J.; Hooton, Steven P.; Sands, Kirsty; Walsh, Timothy R.; Orbegozo Rubio, Claudia; Portal, Edward A. R.; Hudson, Christopher; Stekel, Dov J.; Dodd, Christine E. R.; Hobman, Jon L. (Frontiers in Microbiology, 2025)
Third-generation cephalosporin-resistant Enterobacterales are ranked second on the World Health Organisation (WHO)’s Bacterial Priority Pathogens List. Amongst them, extended-spectrum β-lactamase-producing Escherichia coli (ESBL-Ec) are used by the WHO as sentinel organisms to monitor the spread of antibiotic resistance worldwide and are often associated with mobilisable multidrug resistance (MDR). However, we know less about how ESBL-producing genes spread in environmental E. coli. This study investigates how the blaCTX-M-15 gene from ESBL-Ec isolated on a UK dairy farm could transfer between strains. For this study, 39 E. coli were isolated from a single dairy farm over 4 months, using cefotaxime-supplemented selective media. All had similar antibiotic susceptibility test phenotypes, and PCR, whole genome sequencing (WGS), and resistance gene transmission experiments demonstrated they were all closely related. In silico multi-locus sequence typing and single-nucleotide polymorphism analysis showed that all 39 strains were Sequence Type 2325, but plasmid carriage differed. In total, 35 of the 39 ESBL-Ec strains were multidrug resistant, displaying blaCTX-M type cephalosporin resistance and resistance to fluoroquinolones and tetracyclines. WGS confirmed all 39 isolates carried the ISEcp1 mobile genetic element carrying the blaCTX-M-15 ESBL-producing gene, and the qnrS1 partial quinolone resistance gene in the chromosome. A total of 35 strains also carried tetAR within this ISEcp1 element. We found that sub-lethal levels of ampicillin, cloxacillin, and ceftazidime could enhance the transfer of ISEcp1 blaCTX-M-15 from the chromosome of these dairy farm strains into endogenous self-transmissible plasmids, which can themselves then transfer into and confer phenotypic antibiotic resistance in a recipient E. coli K-12 strain. In conclusion, we observed not only clonal dissemination of these environmentally occurring ESBL-producing strains within the farm environment but also showed experimentally that these strains had the ability to mobilise their ESBL producing genes, and that these and other resistance genes can be acquired or lost on transfer. This shows the importance of longitudinal monitoring of antibiotic resistance, especially in places with high prevalence or selective pressure for resistant bacteria.